PENGEMBANGAN PERANGKAT PEMBELAJARAN BERFIKIR KRITIS APLIKASI PERANGKAT LUNAK DAN DESAIN INTERIOR BANGUNAN DI SMK - Musnaeni; Purnamawati; Abdul Muis Mapalotteng (SEMINAR NASIONAL DIES NATALIS 62, 2023)
The objectives of this research are (1) to analyze the needs for the development of critical thinking learning tools for software applications and building interior design in vocational schools. (2) Describe product validation of critical thinking software applications and interior design of buildings in SMK. (3) Describe the effectiveness of critical thinking products in software applications and interior design of buildings in Vocational High Schools. (4) Describe the practicality of critical thinking products for software applications and building interior design in Vocational High Schools. The type of research used is research and development (Research and Development) which aims to develop and produce a product. The development procedure refers to the ADDIE development model. The results obtained are the development of critical thinking learning tools in the subject of Software Applications and Building Interior Design. The research instrument uses an assessment sheet according to 2 expert lecturers and 25 student responses. The results of the validity, practicality and effectiveness that have been obtained are: 94% material validity, 91.7% practicality and 80% effectiveness.